2008
DOI: 10.1002/app.28865
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Pd catalyst for oxidative carbonylation of bisphenol A to polycarbonate

Abstract: Polycarbonates (PCs) were prepared by oxidative carbonylation of bisphenol A and carbon monoxide, using a Pd-polybipylidyl complex, Pd-polyvinylpyridine complex, smectite-supported Pd complex, or hydrotalcite-supported Pd complex as a heterogeneous Pd catalyst to separate the PC solution and the Pd catalyst after the reaction. Propylene carbonate was used as a halogen-free solvent. When Co(OAc) 2 Á4H 2 O was used as the inorgano-redox catalyst, all of the Pd compounds gave a good PC yield with the recycling po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…As with homogeneous catalysts, propylene carbonate could be used for heterogeneous Pd-catalyzed carbonylations to form polycarbonates of bisphenol A . Furthermore, with the combination of Co(OAc) 2 ·H 2 O as an oxidative cocatalyst and a polymer-supported Pd catalyst, a recyclable carbonylation catalyst was obtained . A study on the kinetics of hetereogeneous, enantioselective hydrogenations with platinum on alumina (Pt/Al 2 O 3 ) and a chiral dihydrocinchonidine was conducted by Gamez et al The rates of the reactions were compared by running the transformations in nonpolar (toluene), polar protic (EtOH), and polar, aprotic solvents (PC).…”
Section: Catalysis In Organic Carbonatesmentioning
confidence: 99%
“…As with homogeneous catalysts, propylene carbonate could be used for heterogeneous Pd-catalyzed carbonylations to form polycarbonates of bisphenol A . Furthermore, with the combination of Co(OAc) 2 ·H 2 O as an oxidative cocatalyst and a polymer-supported Pd catalyst, a recyclable carbonylation catalyst was obtained . A study on the kinetics of hetereogeneous, enantioselective hydrogenations with platinum on alumina (Pt/Al 2 O 3 ) and a chiral dihydrocinchonidine was conducted by Gamez et al The rates of the reactions were compared by running the transformations in nonpolar (toluene), polar protic (EtOH), and polar, aprotic solvents (PC).…”
Section: Catalysis In Organic Carbonatesmentioning
confidence: 99%
“…The redox cocatalysts are necessary to form Pd(II) again by oxidation of Pd(0) through reductive elimination of the carbonate structure. As the inorganic redox cocatalyst, Co, which produces a good PC yield,5–7 was selected. Through the use of the heterogeneous Pd–Co bimetal catalyst, it is possible to separate the PC solution and the Pd–Co bimetal catalyst after the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We found that heterogeneous Pd catalysts have recycling potential. 7 This article describes the oxidative carbonylation of BPA to PC using propylene carbonate and catalyzed by heterogeneous Pd-Co bimetal compounds. As heterogeneous bimetal catalysts, Pd-Co catalysts supported by inorganic layered compounds (smectite and hydrotalcite) and Pd-Co catalysts supported by polymers [poly(4-vinylpyridine) (p-4vpy), polystyrene-supported triphenylphosphine (PS-TPP), and polyvinylpyrrolidone (pvp)] were used so that we could examine their PC yields, catalyst recycling potential, and turnover number (TON).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly attributed to the high solubility of CO in cyclic carbonates. Okamoto’s group has done extensive research on the application of propylene carbonate as an advantageous solvent for the synthesis of polycarbonates by oxidative carbonylation of bisphenol A. Propylene carbonate is also known to stabilize palladium clusters/colloidal palladium accessible from bulk palladium and has been applied for Sonogashira cross-coupling of aryl chlorides and cyclocarbonylation reactions . Recently, we have reported the Pd/C-catalyzed phenoxycarbonylation of aryl iodides under CO surrogacy in propylene carbonate as a sustainable solvent .…”
Section: Introductionmentioning
confidence: 99%